Implementasi Program Bantuan Sosial Pemberian Makanan Gratis Bagi Warga Miskin di Kabupaten Sidoarjo - Fernanda, Tiara; Arif, Lukman (Universitas Muhammadiyah Sorong, 2023)
The free food program for the poor in Sidoarjo Regency is a form of social protection and security carried out by the Sidoarjo Regency Government in the form of food for the poor so that they can maintain a healthy and prosperous condition. This study aims to determine and analyze the implementation of a social assistance program providing free food for the poor in Sidoarjo Regency. The research was conducted using a descriptive qualitative research method using the analysis model of Policy Implementation theory by David C. Korten, based on three elements of research focus, namely 1) Program, 2) Implementing Organization, and 3) Target Group. Data collection techniques using observation, interviews and documentation. The results of this study indicate that the implementation of the social assistance program providing free food for the poor in Sidoarjo Regency has been going well, but it has not been optimal and improvements are needed in several matters related to program implementation